Recent Development of Grid-Connected Microgrid Scheduling Controllers for Sustainable Energy: A Bibliometric Analysis and Future Directions - Mannan M.; Mansor M.; Reza M.S.; Roslan M.F.; Ker P.J.; Hannan M.A. (Institute of Electrical and Electronics Engineers Inc., 2025)
This study presents a comprehensive bibliometric analysis of grid-connected microgrid (MG) scheduling controller techniques. An extensive search was done in the Scopus database using preset parameters to extract articles relating to the MG scheduling controller. The selection of the most cited paper involved careful keyword filtering on grid-connected MG scheduling controllers over the period from 2013 to 2024. Within the timeframe, a total of 115 top-cited articles were extracted, focusing on the scheduling controller algorithms applied to the grid-connected MG system. These highly cited articles originated from a diverse source, encompassing 49 distinct journals, spanning 28 different regions, and representing the publications of 7 distinct publishers. This paper seeks to identify and analyze the highly referenced published articles in the relevant area to yield an in-depth analysis of advanced controllers and optimization strategies in MG energy management systems. The key challenges such as power electronic interface, quality, controller, safety and optimization were also highlighted to provide the clearest insight on the recent MG development. Valuable recommendations for future research directions are also provided, aimed at promoting the sustainable growth of MGs. A substantial total of 63.56% articles were published based on simulation while 18.6%, 13.95% and 3.87% of total articles were published on the experimental setup, critical analysis and review-based study. Therefore, it can be inferred that ongoing research and development efforts continually seek to improve the sustainability of MG systems within the electric power sector. The bibliometric analysis was employed to identify pivotal research publications concerning grid-connected MG scheduling controller technique. This analysis aimed to delineate the multidisciplinary nature, illustrate trends, and outline areas warranting further research in the field. Thus, to ensure an effective, economical, reliable, and sustainable power supply, this analysis will broaden the scope and offer context for the development of MG scheduling controller integrated grid systems. ? 2024 IEEE.